2011
DOI: 10.1159/000334599
|View full text |Cite
|
Sign up to set email alerts
|

A Q Fever Outbreak in the Netherlands: Consequences for Tissue Banking

Abstract: Background: Emerging infectious diseases can compromise the safety of tissues for transplantations. A recent outbreak of Q fever, a zoonosis caused by the bacterium Coxiella burnetii, in the Netherlands compelled the Dutch tissue banks to assess the risk of Q fever transmission through tissue transplantation in order to maintain optimal safety. Methods: This article describes the systematic approach that was followed in the Netherlands. This approach included a review of the literature, a qualitative risk asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…After the acute phase, bacteria are usually not detectable in the blood, but they can persist in monocytes, bone marrow, spleen, prostate and liver [ 14 ]. An assessment showed that a potential risk of transmitting C. burnetii lies with transplantation of some tissues such as heart valves, musculoskeletal tissues and skin, although processing techniques may reduce the risk significantly [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the acute phase, bacteria are usually not detectable in the blood, but they can persist in monocytes, bone marrow, spleen, prostate and liver [ 14 ]. An assessment showed that a potential risk of transmitting C. burnetii lies with transplantation of some tissues such as heart valves, musculoskeletal tissues and skin, although processing techniques may reduce the risk significantly [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the chronic course, DNA can be detected periodically years after acute infection, and antibody titers remain high. Diagram based on Van Wijk et al, 2011 [134] (L. Guertler). …”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%
“…as PCR, is not routinely performed and, considering the current epidemiological situation, not necessary. In blood donors in the Netherlands, 1,004 donors in the area with the highest C. burnetii incidence were tested using PCR, and 3 (0.3%) were identified as being genome-positive [134]. The strategy shows that NAT can be introduced if required.…”
Section: Blood and Plasma Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper the extent of infection and the safety of local blood donations were tested for presence of Coxiella burnetii antibodies and DNA [2]. The impact of the Q fever outbreak for tissue donations was discussed by van Wijk et al [3] in their contribution.…”
mentioning
confidence: 99%